Isaura Lamouroux, in Audouin, Bourdon, de Candolle, d’Aubebard de Férussac, Deshayes, Deslongchamps, É. Geoffroy Saint-Hilaire, I. Geoffroy Saint-Hilaire, Guérin, Guillemin, de Jussieu, Kunth, Delafosse, Lamouroux, Latreille, Prévost, Richard & Bory de Saint-Vincent, 1826, an available name and objective synonym of Isaurus Gray, 1828: reversal of precedence (Cnidaria: Anthozoa: Hexacorallia) - Low, Martyn E. Y.; Reimer, James Davis (Zootaxa, 2012)
Savigny (1811: pl. 2, figs. 1–4, caption) presented four species of zoanthids which he referred to as “Isaures fixées” in French (not Latin) in his work on cnidarians from Egypt. Audouin (1826: 229–231) later wrote the text to accompany Savigny’s (1811: pl. 2) plates, when the latter’s health failed (see Sherborn 1897: 287).